Contraceptive and medical possibilities of estrogen-hestagenic preparations - T V Ovsiannikova; I A Kulikov (IP Berlin A.V., 2017)
The article presents data on reproductive health problems in women of late reproductive and perimenorausal age. The indications and optimal methods of contraception in this age period have been refined. It was noted that the individual approach and correctly selected COCs in the late reproductive and perimenopausal periods provide reliable contraception and have a curative effect in endometrial hyperplasia, dysmenorrhea, AMC, hyperandrogenism and PMS. Contraceptive and therapeutic aspects of the use of Lindineth 20 are considered. The use of COC with age, gynecological and extragenital diseases reduces the frequency of the formation of functional ovarian cysts and benign breast diseases and the risks of development of ovarian, endometrial and colorectal cancer in the future.